ASESMEN TINGKAT KERUSAKAN AKIBAT MIKROORGANISME SEPANJANG RANTAI PASOK BUAH TOMAT DI KABUPATEN MERAUKE - Hasria Hasria; Jamaludin Jamaludin; Yus Witdarko (Faculty of Agriculture, Musamus University, 2021)
Improper post-harvest handling of tomatoes in the supply chain can cause damage due to microorganisms. This damage has a loss on the post-harvest process of each supply chain actor. The purpose of this study is to identify the degree of damage to tomatoes due to the activity of microorganisms along the supply chain. The method used in this study is the purposive sampling method, which is to determine tomato supply chain patterns, and the Snowball sampling method to obtain the next culprit. The results obtained in this study are that there are 5 supply chain patterns in Merauke Regency. The longest tomato supply chain pattern is found in the supply chain pattern to V and the shortest pattern is in the third supply chain pattern. Post-harvest handling starts from farmers, collectors, small traders to the hands of consumers. Losses on tomatoes occurred along the supply chain by 2.07% with details at the farmer stage of 0.94%, the collector stage by 0.64%, the small trader stage by 0.49%, and the consumer stage by 0%. The isolation results obtained eight types of fungi, namely Rhizoctonia solani (45%), Fusarium sp (23%), Trichoderma sp (14%), Cladosporium sp (8%), Rhizopus (4%), Drechslera sp (2%), Stachybotrys ( 2%), Curvularia sp (2%). Based on the percentage of findings, the fungi that were the main cause of tomato fruit rot were the fungi Rhizoctonia solani and Fusarium sp.